Berpengaruhkah Pendapatan Asli Daerah Dan Belanja Modal Terhadap Indeks Pembangunan Manusia? - Yarsalna Faturani; Elva Dona (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this study was to examine the effect of regional original income and capital expenditure on the human development index in the districts/cities of West Sumatra in 2016-2021. The object of this research is the district/city government of West Sumatra. The data used is secondary data taken from reports on the realization of local government revenues at the West Sumatra Central Bureau of Statistics (BPS). The type of data used is panel data. The population and sample are 19 districts/cities of West Sumatra using the total sampling technique. The results of the study show that Regional Original Income and Capital Expenditures have a significant effect on the Human Development Index.